Educating for social responsability through experiential service learning course - Vizek-Vidović, Vlasta (Array, 2003)
The aim of the paper is to present the implementation and evaluation of the new one semester optional course "Mainstreaming students with special needs" offered to the 4th year undergraduate psychology students. The course design has been based upon the concept of the education for social responsibility. The main goal of the course was defined as the development of empathy and sensibilisation of the students for the issues concerning the mainstreaming of children with special needs within regular classrooms. The experiential learning was enhanced using the case-study approach through field assignments in the classrooms and referral institutions. The project assignment (carried out in small groups of 4-5 students) consisted of four phases: designing the case study, collecting data, preparing and presenting the report. At the end of the course the students evaluated following aspects: course plan and lecture organization, motivation and learning opportunities, relationships with participants in the teaching process and the global satisfaction with the course. Students were also asked to rate on the several comparable subscales "the typical" and "traditional course". The data analysis showed that students had very positive reactions to the new course giving it significantly higher ratings then to the course of traditional design. It is interesting to note that the lowest ratings were given to their participation in the teamwork, although in their commentaries they also pointed out the importance of that learning experience. It has been concluded that more attention should be paid to the process aspect of the course.